(untitled) - Dunn, Viviane (Oxford, 1996)
This book introduces and develops the strategies and skills necessary for understanding fifferent types of authentic spoken English.
Keywords: Tiếng Anh,English language,English language,Tiếng Anh; Giáo trình dành cho người nước ngoài,Listening,Textbooks for foreign speakers,Kỹ năng nghe